2013
DOI: 10.1016/j.matdes.2012.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of the strain rate on the compressive response of a closed-cell aluminium foam using the split Hopkinson pressure bar test

Abstract: Evaluation of the effect of the strain rate on the compressive response of a closed-cell aluminium foam using the split Hopkinson pressure bar test Citation for published version: Irausquín, I, Pérez-Castellanos, JL, Miranda, V & Teixeira-Dias, F 2013, 'Evaluation of the effect of the strain rate on the compressive response of a closed-cell aluminium foam using the split Hopkinson pressure bar test', Materials and Design, vol. 47, pp. 698-705. https://doi.Evaluation of the effect of the strain rate on the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…It can be seen that the dynamic strength and the dynamic plateau stress increase with the increase of strain rate. The numerical results are consistent with the test observations [28] at the strain rates of 5 Â 10 2 s À1 and 9 Â 10 2 s À1 . It can be concluded that the numerical model presented in this paper can give reliable predictions of closed-cell aluminum foams subjected to high strain rates.…”
Section: Dynamic Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…It can be seen that the dynamic strength and the dynamic plateau stress increase with the increase of strain rate. The numerical results are consistent with the test observations [28] at the strain rates of 5 Â 10 2 s À1 and 9 Â 10 2 s À1 . It can be concluded that the numerical model presented in this paper can give reliable predictions of closed-cell aluminum foams subjected to high strain rates.…”
Section: Dynamic Propertiessupporting
confidence: 88%
“…The pore size, R min and R max , is 0.9 mm and 3.8 mm. The average pore size is 2.6 mm and the pores ratio is 87.1%, according to the test [28]. The computational parameters for the cell-wall and the air are the same as in Section 4.1.…”
Section: Dynamic Propertiesmentioning
confidence: 99%
“…To show the relationship between the normalized plateau force and the loading velocity, the dynamic plateau forces diveded by quasi-stiac value of all specimens are plotted in Fig. 8, as well as the data from Irausquin et al [7] They evaluated the dynamic behaviour of closed-cell aluminum foam ALPORAS 10% using SHPB. In both our tests and Irausquin's tests, there is a significant increase in the specific plateau forces with the increasing velocity between 10 m/s∼30 m/s.…”
Section: Compression and Indentation Forcesmentioning
confidence: 99%
“…On the other hand, according to Gibson and Ashby [8], Dashpande and Fleck's [6] research, the contribution of gas trapped in cells is so small as to be negligible for this increase. Microinertia effects of the cell walls [7,9] or the plastic wave [10] may cause this phenomenon. Further discussion will be conducted in FEM analysis.…”
Section: Compression and Indentation Forcesmentioning
confidence: 99%
“…In SHPB test, depending on the bar materials and configurations, different strain rates were obtained and seek to achieve different objectives. Viscoelastic bar [11], magnesium alloy bar [12], and hollow aluminium tube bar [13] were used as Hopkinson pressure bar to match the low mechanical impedance of closed-cell aluminium foams and increased the amplitude of the strain signal measured by the strain gauges attached to the bar. To overcome the small specimen and small strain level conducted using SHPB, a novel modified SHPB configuration [14] used 50 mm diameter aluminium tubular bar with long pre-stress bar that replaced the striker bar that was typically used in SHPB test to obtain a specimen strain up to 50% due to the generated longduration pulse.…”
Section: Introductionmentioning
confidence: 99%